Legal Protection for Foreign Investors in Mining Activities According to Regulations Legislation in Indonesia - Mygen Flintandyo; Arrum Budi Leksono (Sean Institute, 2025)
The mining sector is a key pillar of the Indonesian economy, contributing significantly to state revenue and employment. Indonesia's abundant natural resource potential makes it a strategic destination for foreign investors in the mining sector. However, the investment climate in this sector still faces various challenges, such as regulatory uncertainty, expropriation, and legal conflicts. This study aims to analyze the forms of legal protection provided to foreign investors in mining activities in Indonesia. The research method used is a normative juridical approach with a statutory approach. The results show that legal regulations related to foreign investment in the mining sector are based on the principles of legal certainty and fair treatment, strict but transparent licensing, guarantees of ownership and return of capital, and social and environmental obligations. These regulations include provisions related to the legality of business entities, general licensing, and share ownership. Forms of legal protection for foreign investors in the mining sector include protection against nationalization, legal certainty through business permits, fair and equal treatment, and access to national and international dispute resolution mechanisms. All of these instruments aim to build a stable and attractive investment climate for foreign capital.